Toward a review of research and knowledge in Philippine public administration - Ocampo, Romeo B. (1982)
A review of what has been attempted to be known and what has been known about Philippine Public Administration can be put in a framework of thirty years of research, worthwhile questions, and preliminary hypotheses. At the College of Public Administration, public policy and program administration have provided a link between line and staff subject matters, and between the focus on governmental administration and the concern with national development problems and processes. Worthwhile questions on Philippine Public Administration range from the policy-prescription' type to administration-oriented prescriptive category. Seven "hypotheses" or initial guesses about the thrusts of Public Administration research in the Philippines and tentative assessments of its accomplishments provide a comprehensive summary of the state of the "science."
Keywords: Public administration; Public administration -- Research